Oil Price and Economic Growth Nexus in Saudi Arabia: Asymmetry Analysis - Mahmood, Haider; Murshed, Muntasir (International Journal of Energy Economics and Policy, 2020)
Oil Price (OP) and revenue play a significant contribution to the income of oil producers. Saudi income is majorly sourced from the oil sector. Therefore, it is very important to see the influence of OP on income. Particularly, testing asymmetry is necessary to see whether increasing OP has the same effect on income or not as of decreasing OP. This present research cares about this issue using nonlinear cointegration techniques. We found the symmetrical effect of OP on income in the long-run and asymmetrical effects in the short-run. Moreover, increasing and decreasing OP have equal pleasant and harmful effects on income. Moreover, increasing OP has a more pleasant effect than that of decreasing OP harmful effects on income in the short-run. Keywords: Asymmetry, Oil price, Economic growth, cointegration JEL Classifications: Q41, O47, C12 DOI: https://doi.org/10.32479/ijeep.10382